2019
DOI: 10.31557/apjcp.2019.20.8.2455
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Epithelial to Mesenchymal Transition Related Genes by Lipopolysaccharide in Human Cervical Cancer Cell Line HeLa

Abstract: Objective: Cancer is one of the common diseases in the world, and cervical cancer is the fourth one. In this type of cancer, many risk factors, especially infectious diseases, such as human papilloma virus (HPV) and gram-negative bacteria can have important effects on the expression of epithelial to mesenchymal transition related genes like Snail, E-cadherin, and ZEB-1, responsible for connecting cell tissues. In this study, we have investigated the effect of Escherichia coli O111:B4 Lipopolysaccharide (LPS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…The inverse correlation between Slug and p16 positivity, as a marker for human papilloma virus (HPV) infection, requires adjustment for p16 effects when examining the clinical effects of Slug expression ( p = 0.012). There are several studies in HPV positive cervical cancer cells (especially HeLa cells) that report that the HPV related oncogenes E6 and E7 might repress E-cadherin expression independent of Slug and consequently induce EMT in cervical cancer [ 50 , 51 , 52 , 53 , 54 ]. In HNC the association between HPV status and EMT is even less known, but the results also support a positive association between HPV status and EMT in vitro [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inverse correlation between Slug and p16 positivity, as a marker for human papilloma virus (HPV) infection, requires adjustment for p16 effects when examining the clinical effects of Slug expression ( p = 0.012). There are several studies in HPV positive cervical cancer cells (especially HeLa cells) that report that the HPV related oncogenes E6 and E7 might repress E-cadherin expression independent of Slug and consequently induce EMT in cervical cancer [ 50 , 51 , 52 , 53 , 54 ]. In HNC the association between HPV status and EMT is even less known, but the results also support a positive association between HPV status and EMT in vitro [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence confirmed that various genes, such as E-cadherin, Snail, and ZEB-1 are known as EMT-related genes. It has been shown that deregulation of these genes is associated with metastasis and other cancer -related processes (Tavakolian et al, 2019;Brabletz et al, 2018). In a study, Chen et al, indicated that expression of E-cadherin is associated with the metastasized lymph node (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another HERV-associated gene whose its expression was elevated in malignant tissues was HERV-k np9 . There are several reports claiming that the expression level of this gene is increased in a variety of human cancers, ranging from solid tumors, such as breast cancer [25, 29] and melanoma [30], to chronic hematologic malignancies [31]. The oncogenic property of np9 is also evident in transformed cell lines, where it has been reported that this gene could serve as a growth factor for cancer cells [32].…”
Section: Discussionmentioning
confidence: 99%